A study on learning styles of secondary school student's according to gender and class level - Bayrak, Beyza Karadeniz (ELSEVIER SCIENCE BV, 2012)
The purpose of this study is to determine the effect of some personal characteristics such as age, gender of the secondary school students on their learning styles. The learning styles inventory that was developed by Grasha (1994) was applied to the participants. The learning styles inventory involved 6 sub-scales as independent, collaborative, competitive, avoidant, participant and dependent. The students' learning styles prefences were analyzed through frequency (f) and percentages (%). Students' learning styles preference was compared with gender, class level by using Chi-square Test. According to the results of the study; it was found that 48,2% of the secondary school students participating in the study have competitive, 29,2% of them have collaborative, 10,9% independent, 4,5% avoidant, 4,5% participant and 2,7% dependent learning styles. There was a significant difference between the students' learning styles and student's gender (p 0,05). (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Learning styles; secondary school; student; Education & Educational Research